2020
DOI: 10.1038/s43246-020-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Crystallisation control of drop-cast quasi-2D/3D perovskite layers for efficient solar cells

Abstract: Introducing layered quasi-2D perovskite phases into a conventional 3D perovskite lightabsorbing matrix is a promising strategy for overcoming the limited environmental stability of 3D perovskite solar cells. Here, we present a simple drop-casting method for preparing hybrid perovskite films comprising both quasi-2D and quasi-3D phases, formed using phenylethylammonium or iso-butylammonium as spacer cations. The film morphology, phase purity, and crystal orientation of the hybrid quasi-2D/3D perovskite films ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 46 publications
1
69
0
Order By: Relevance
“…Recently, researchers found that the introduction of long‐chain organic cations in 3D perovskite as 2D perovskite can block water and oxygen molecules, meanwhile, generate a steric effect to prevent phase transitions, and limit ion migration. [ 34–36 ] Hence, fabricating 2D [ 37,38 ] or 2D/3D [ 39–43 ] mixed perovskite as absorbing layers are effective approaches to improve the stability of PSCs. However, the PCE of 2D PSCs remain lower than that of the 3D ones, which is mainly attributed to the introduction of organic macromolecules that blocks the effective extraction and transport of carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers found that the introduction of long‐chain organic cations in 3D perovskite as 2D perovskite can block water and oxygen molecules, meanwhile, generate a steric effect to prevent phase transitions, and limit ion migration. [ 34–36 ] Hence, fabricating 2D [ 37,38 ] or 2D/3D [ 39–43 ] mixed perovskite as absorbing layers are effective approaches to improve the stability of PSCs. However, the PCE of 2D PSCs remain lower than that of the 3D ones, which is mainly attributed to the introduction of organic macromolecules that blocks the effective extraction and transport of carriers.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Drop-cast MAPbI 3 films consisted of needle-like crystals, leading to low device performance. [19] Improving the morphology of drop-cast MAPbI 3 films is an effective way to realize higher device performance. In this work, we regulate the growth of MAPbI 3 crystals in the film made by dropcasting.…”
Section: Perovskitesolarcellsaregettingclosertocommercializationmentioning
confidence: 99%
“…Recently, we prepared two‐dimensional (2D) Ruddlesden–Popper perovskite films by using drop‐casting [18, 19] . This method was performed in air, and it is suitable for in situ study of crystal growth.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations